Electrochemotherapy as a Trigger to Overcome Primary Resistance to Anti-PD-1 Treatment: A Case Report of Melanoma of the Scalp - Davide Quaresmini; Alessandra Di Lauro; Livia Fucci; Sabino Strippoli; Ivana De Risi; Angela Monica Sciacovelli; Anna Albano; Gaetano Achille; Massimo Montepara; Sabino Russo; Gabriella Tassone; Michele Guida (Frontiers in Oncology, 2021)
BackgroundImmunotherapy with immune checkpoint inhibitors is one of the main therapies for advanced melanoma. Nevertheless, albeit remarkable, immunotherapy results are still unsatisfactory as more than half of patients progress, and resistance to treatment still has a dramatic impact on clinical outcomes. Local treatments such as radiotherapy or electrochemotherapy (ECT), in addition to local control with palliative intent, have been shown to release tumoral neoantigens that can stimulate a robust systemic antitumor immune response.Case PresentationWe report the case of a patient with multiple nodular melanoma lesions of the scalp initially treated with local ECT. Soon after the procedure, multiple new lesions appeared close to the treated ones, therefore the patient started a systemic treatment with the anti-PD-1 nivolumab. The lesions of the scalp did not respond to immunotherapy, presenting a loco-regional spreading. To control the bleeding and painful lesions, we performed a second ECT, while continuing systemic immunotherapy. The treated lesions responded to the second procedure, while the other lesions continued progressing in number and dimension. Unexpectedly, after 2 months from the second ECT, the patient presented a progressive shrinkage of both treated and untreated lesions until complete remission. Concomitantly, he developed immune-related adverse events including grade 4 thyroid toxicity, grade 2 vitiligo-like depigmentation and grade 2 pemphigoid. At present, after 18 months from the first ECT and 14 months from the starting of anti-PD-1 immunotherapy, the patient is in good clinical condition and complete remission of disease still persists.ConclusionThis case highlights the potential role of ECT in increasing tumor immunogenicity and consequently in inducing a powerful immune response overcoming primary resistance to checkpoint inhibitor immunotherapy.